THE DAMAGE ZONE-FAULT CORE TRANSITION IN CARBONATE ROCKS: IMPLICATIONS FOR FAULT GROWTH, STRUCTURE AND PERMEABILITY - Billi A.; Salvini F.; Storti F. (My University, 2003)
We studied the nucleation and growth of cataclastic fault cores from fractured damage zones in extensional and strike-slip fault zones in carbonate rocks. Analysed fault zones have similar protolith lithology and sedimentary fabric, but different geometry, kinematics, size, tectonic environment and deformation history. Orthorhombic rock lithons, a few decimetres in size, characterise the structural fabric of damage zones. Lithons derive from the intersection of a dominant fracture/cleavage set with bedding and/or joints. At the damage zone-fault core transition, orthorhombic lithons reduce in size and approach an isometric shape. Their cross-sectional aspect ratio has an average value of 1.4. Analysed fault cores have similar rock textures, sorting and comminution degree. Particle-size distributions of fault core rocks show linear trends in log-log graphs and average fractal dimension of 2.5. Our results on rock fabrics suggest that fault core development initiates from rock masses in damage zones, where the shape anisotropy of orthorhombic lithons favours additional fracturing at high angle to their long axes. Eventually, smaller, nearly isometric lithons generate from repeated fracturing of orthorhombic lithons. When the aspect ratio of these lithons approaches the threshold value of about 1.4, particle rotation is favoured and cataclastic flow starts. Owing to the granular nature of the damage zone-fault core transitions in carbonate rocks, analogies with the nucleation of deformation bands in sandstones can be established. Our results may be of use to the industry for quantitative characterisation of fault zone permeability. According to the proposed model, radical changes on the permeability properties are expected during the growth of fault cores.
Keywords: FAULT CORE; DAMAGE ZONE; DAMAGE ZONE-FAULT CORE TRANSITION; STRUCTURAL FABRIC; ROCK LITHON; PARTICLE-SIZE DISTRIBUTION